Study on Finite-time Fault-tolerant Control for a Robot Manipulator Based on Synchronous Terminal Sliding Mode Control - Quang Dan Le; Hee-Jun Kang (New Approaches in Engineering Research Vol. 13, 2021)
In this paper, two finite-time active fault-tolerant controllers for a robot manipulator, which combine a synchronous terminal sliding mode control with an extended state observer, are proposed. First, an extended state observer is adopted to estimate the lumped uncertainties, disturbances, and faults. The estimation information is used to compensate the controller designed in the following step. We present an active fault-tolerant control with finite-time synchronous terminal sliding mode control, largely based on a novel finite-time synchronization error and coupling position error. We also present an active fault-tolerant control that does not use a coupling position error. By using synchronization control, the position error at each joint can simultaneously approach toward zero and toward equality, which may reduce the picking phenomenon associated with the active fault-tolerant controller strategy. Finally, simulation and experimental results for a three degree-of-freedom robot manipulator verify the effectiveness of the two proposed active fault-tolerant controllers.